2016
DOI: 10.2217/rme-2016-0065
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Properties of the Spinal Cord: Implications for Tissue Engineering and Clinical Translation

Abstract: Spinal cord injury is a severely debilitating condition which can leave individuals paralyzed and suffering from autonomic dysfunction. Regenerative medicine may offer a promising solution to this problem. Previous research has focused primarily on exploring the cellular and biological aspects of the spinal cord, yet relatively little remains known about the biomechanical properties of spinal cord tissue. Given that a number of regenerative strategies aim to deliver cells and materials in the form of tissue-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 94 publications
1
26
0
1
Order By: Relevance
“…strain of tensile measures 59 or frequency of oscillatory rheology 60 ) can affect the modulus of elasticity determined. Notably, higher strain increases the measured modulus of elasticity 61 , 62 but changes in strain rate have been reported not to have an effect 58 (for a review see Bartlett et al, 63 ). For example, bovine spinal cord white matter measured by tensile measurement was reported to have a modulus of elasticity of 1.05 MPa with a strain of 40% and 115 kPa with a strain of 5% in the same study.…”
Section: Discussionmentioning
confidence: 99%
“…strain of tensile measures 59 or frequency of oscillatory rheology 60 ) can affect the modulus of elasticity determined. Notably, higher strain increases the measured modulus of elasticity 61 , 62 but changes in strain rate have been reported not to have an effect 58 (for a review see Bartlett et al, 63 ). For example, bovine spinal cord white matter measured by tensile measurement was reported to have a modulus of elasticity of 1.05 MPa with a strain of 40% and 115 kPa with a strain of 5% in the same study.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue engineering is rather demanding, it requires looking not only from the crosslinking rate perspective, but also from a mechanical and biological point of view. For lower MC concentrations, the final storage modulus (DMA) s comparable to native human tissues such as liver [13], spinal cord [14], or cartilage [33]. From biological tests, it was found that at low concentrations, MC provided a good cellular response and non-toxic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Considering its effective support in cells regeneration [8] and having been approved by the Food and Drug Administration (USA), MC is an attractive material for tissue engineering or drug delivery systems [9]. Contrary to other natural hydrogels (e.g., alginate), MC constitutes a stable structure in physiological conditions, with mechanical properties similar to native tissues (e.g., meniscus, liver, or spinal cord) [10,11,12,13,14]. From the perspective of tissue engineering, the thermosensitive crosslinking of MC aqueous solution seems very promising, as it prevents the use of toxic crosslinking agents [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is essential that any tissue engineered therapy for spinal cord injury is designed with desirable mechanical characteristics in order to avoid implant-induced damage and to, maximize cellular response, regeneration and functional recovery 43 . Whilst biomechanical studies of spinal cord tissue have reported a range of modulus values (0.12–15.2 kPa) 44 , depending upon species and measurement methods, low stiffness and viscoelasticity are key parameters in selection of appropriate biomaterials. All the hydrogels assessed in this study had maximum moduli less than 1 kPa and meet these requirements.…”
Section: Discussionmentioning
confidence: 99%